Trade Disruptions Along the Global Supply Chain - Alejandro G. Graziano; Yuan Tian (Centre for Inclusive Trade Policy (CITP), University of Sussex Business School, 2023)
In 2020, a pandemic generated by a novel virus caused a large and abrupt decline in world trade, only comparable within the last half-century to the great trade collapse during the 2008-09 financial crisis. This collapse followed naturally from the difficulty of locally producing, transporting, and consuming goods in the affected regions worldwide. In this paper, the authors study the impact of these disruptive local shocks on international trade flows during the COVID-19 pandemic. Using rich product-level import data from Colombia, we first show that import collapse at the onset of the pandemic was due to a decrease in import quantities, and the import recovery in later periods was partially explained by a rise in both foreign export prices and shipping costs. Using smartphone data tracking of local human mobility changes to identify local shocks, the authors decompose the trade effects into shocks originating from exporter cities, seaports, and importer cities. They find that while the decline in quantity was driven by both changes in exporter and importer shocks, the increase in price was entirely driven by exporter shocks. Using data on port calls made by container ships, they document a decline in port productivity during the pandemic. The authors show that mobility changes at port locations induced a decline in port efficiency and a rise in freight costs. They also document a positive correlation between product-level domestic inflation and mobility shocks to foreign exporters.
Keywords: 330